2009
DOI: 10.1593/neo.09902
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Putative Biomarkers of Radiotherapy Resistance: A Possible Role for the 26S Proteasome?

Abstract: These findings suggest that the 26S proteasome may provide a general predictive biomarker for radiotherapy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 31 publications
0
53
1
Order By: Relevance
“…However, the question remains as to whether these breast cancer subtypes may be used to predict response to RT or whether specific subtypes may benefit from radiosensitising agents to enhance the efficacy of this treatment. Data from our in vitro studies have shown that breast cancer cell lines representing the different subtypes exhibit differential inherent sensitivities to ionising radiation [28], which suggests that this may certainly be feasible. A clear advantage of being able to exploit these markers for selecting patients for RT is that their expression is already routinely analysed within the clinic for diagnostic and prognostic purposes and also for selecting patients for other breast cancer therapies.…”
Section: Breast Cancer Subtypes and Response To Radiotherapymentioning
confidence: 94%
“…However, the question remains as to whether these breast cancer subtypes may be used to predict response to RT or whether specific subtypes may benefit from radiosensitising agents to enhance the efficacy of this treatment. Data from our in vitro studies have shown that breast cancer cell lines representing the different subtypes exhibit differential inherent sensitivities to ionising radiation [28], which suggests that this may certainly be feasible. A clear advantage of being able to exploit these markers for selecting patients for RT is that their expression is already routinely analysed within the clinic for diagnostic and prognostic purposes and also for selecting patients for other breast cancer therapies.…”
Section: Breast Cancer Subtypes and Response To Radiotherapymentioning
confidence: 94%
“…It was recently estimated that one-half to two-thirds of cancer patients receive radiation therapy in curative or palliative settings during their disease [1,2]. Radiotherapy is a therapeutic approach with a very high potential for local control: ionizing radiation is equally as effective as surgery in curing prostate [3,4], laryngeal [5], cervical [6], and anal cancers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings indicated the relationship between PSMA7 expression and the clinicopathological features of colorectal cancer and suggested that PSMA7 may be molecular targets for colorectal cancer therapy [5,6,16]. However, it is unknown how PSMA7 critically regulates the tumorigensis of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%